As representações das mulheres em obras pentecostais das igrejas Assembléia de Deus e Universal do Reino de Deus - Berger, Carlos Norberto (2020)
This thesis addresses the interrelationship between how women are represented in Pentecostal publications and the interests of the institutions that publish and disseminate them. The study involved two Pentecostal churches: the Assembly of God Church (IAD) from Classical Pentecostalism, and the Universal Church of the Kingdom of God (IURD) from Neopentecostalism. The study analysed how the representations of women in the Pentecostal publications correspond to the power strategies of the institutions in which they are produced. We sought to identify the relationship between the construction of representations on women in Pentecostal books published by the Publishing House of Assembly of God (CPAD) and the Universal Productions (UNIPRO) and the objectives of the churches involved in these publications. This demanded some procedures: to historicize the displacements and transformations in the religious field since the birth of these institutions; to identify the relationships between the discourses that surface in these works as well as the doctrines of their churches; to understand the connections between the representations of women produced in the works and the power strategies that produce them; to provide visibility to the statements that, in the construction of representations of women, changed dogmas so resilient that today's women can approach them; and, finally, to provide visibility to the consonances and dissonances of the two institutions. A qualitative approach in an interdisciplinary perspective was adopted, so it was possible to analyse these works in the 'junction' of the discourse and of the institutions that, through their publishers, produce and spread their statements. For that purpose the some tools of Discourse Analysis were used. The corpus on which the research was based consists of eleven books published from 2000 and 2017, written by women and aimed at women. Six of them were published by CPAD and five, by UNIPRO, official editors of IAD and IURD, respectively. Representations are understood here as determined by the interests of the groups that forge them, in order to build social desire, norms and values through them. Thus, we state that, although there are dissonances between the works, and the institutions, a discourse aimed at producing essentialist identities prevails, representing women linked to a supposed 'feminine essence' or 'feminine nature', and therefore to an idealized woman. From this perspective, all women are positioned, on the one hand, as more distant or closer to Eve, the sinner, and, on the other hand, as the 'virtuous woman'. The analysis showed that this way of representing women is a way of having them work intensively for the institution. It was found that the construction of this position subsidises the strategies aiming at ordering ecclesiastical life, establishing human groups in different positions of power, so that from each position the maximum is extracted for the machinery that produces and sustains the institution itself. It was concluded that there is a clear interdependence between what is proposed by the representations that these publications make of women and the power strategies of the institutions that published them.